2015
DOI: 10.2466/10.27.pms.120v10x1
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Scores on the Draw-a-Person Test across Childhood: Do They Relate to Graphic Fluency?

Abstract: Girls are said to outperform boys in the human figure drawing, but some disagreement exists among studies regarding such sex differences, and the reasons for these sex differences are unclear. The study examined how sex, age, and graphic fluency affect scores at the human figure drawing in large sample of children aged five to 12 years. To that end, the Draw-a-Person Test was administered to 336 boys and girls from kindergarten to Grade 6, using Goodenough's scoring method. Graphic fluency was measured using T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…For instance, tasks asking children to draw a generic person have often been interpreted as projective measures of children's self‐expression and gender identity (Arteche, Bandeira, & Hutz, ). Consistent with this hypothesis, when asked to draw a person, usually 70% or more of both boys and girls have drawn their own sex in prior studies (Arteche et al., ; Picard, ). Given these results, we predicted that boys in our meta‐analysis would draw male scientists more often than girls.…”
Section: Gender‐science Stereotypes Across Development and Historicalmentioning
confidence: 78%
See 1 more Smart Citation
“…For instance, tasks asking children to draw a generic person have often been interpreted as projective measures of children's self‐expression and gender identity (Arteche, Bandeira, & Hutz, ). Consistent with this hypothesis, when asked to draw a person, usually 70% or more of both boys and girls have drawn their own sex in prior studies (Arteche et al., ; Picard, ). Given these results, we predicted that boys in our meta‐analysis would draw male scientists more often than girls.…”
Section: Gender‐science Stereotypes Across Development and Historicalmentioning
confidence: 78%
“…Most children have positive attitudes toward their own sex (Dunham, Baron, & Banaji, ; Halim, Ruble, Tamis‐LeMonda, Shrout, & Amodio, ) and therefore may draw their own sex as an expression of these attitudes. For instance, when asked to draw a generic person, usually 70% or more of both boys and girls draw their own sex (Arteche et al., ; Picard, ). Our meta‐analysis found similar results for the youngest children included in Draw‐A‐Scientist studies.…”
Section: Discussionmentioning
confidence: 99%
“…When asked to come up with a typical person, women generated a man at chance (45%) while men generated a man almost exclusively (92%, Bailey & LaFrance, 2016a). While tests that instruct children to draw a person consistently find that children tend to draw their own gender (Picard, 2015), one study found that both boys and girls draw more male figures as they age suggesting a possible developmental trajectory (Laosa, Swartz, & Holtzman, 1973).…”
Section: Contexts That Moderate Androcentric Behaviormentioning
confidence: 99%
“…Por otro lado, generalmente se asocia al sexo femenino con un desarrollo precoz y un mayor IFP (Picard, 2015), en este estudio se observaron mayores cifras en el sexo masculino, esto podría deberse a factores psicosociales específicos de la población, ya que el desarrollo de las funciones psicológicas superiores está relacionado con el desarrollo madurativo del cerebro, la educación, la estimulación, las experiencias y las oportunidades de aprendizaje que, de acuerdo con las diversas poblaciones estudiadas, pueden variar. Otro factor que pudiera influir, son las características de la crianza de la región, que tienden a la sobreprotección del sexo femenino, lo que pudiera generar un déficit en la independencia, y repercutir en su IFP, además de posibles efectos emocionales y psicosociales durante su desarrollo (Masud, et al, 2019).…”
Section: Discussionunclassified